1994
DOI: 10.1038/372237a0
|View full text |Cite
|
Sign up to set email alerts
|

Motor deficit and impairment of synaptic plasticity in mice lacking mGluR1

Abstract: Metabotropic glutamate receptor 1 (mGluR1) is a member of a large family of G-protein-coupled glutamate receptors, the physiological functions of which are largely unknown. Mice deficient in mGluR1 have severe motor coordination and spatial learning deficits. They have no gross anatomical or basic electrophysiological abnormalities in either the cerebellum or hippocampus, but they show impaired cerebellar long-term depression and hippocampal mossy fibre long-term potentiation. mGluR1-deficient mice should ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
434
2
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 705 publications
(471 citation statements)
references
References 37 publications
25
434
2
3
Order By: Relevance
“…Therefore, the mGluR1 knockout mouse is the first mouse model whose phenotypes support the notion that LTD at parallel fibre to Purkinje cell synapse is a cellular basis of cerebellum-dependent discrete motor learning. Conquet et al (1994) also reported in the same year that cerebellar LTD was deficient in mice lacking mGluR1. After he returned to Japan, Aiba and co-workers created a mouse strain in which mGluR1 is expressed only in cerebellar Purkinje cells (Ichise et al 2000).…”
Section: Long-term Depression (A) Discovery Of Ltdmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, the mGluR1 knockout mouse is the first mouse model whose phenotypes support the notion that LTD at parallel fibre to Purkinje cell synapse is a cellular basis of cerebellum-dependent discrete motor learning. Conquet et al (1994) also reported in the same year that cerebellar LTD was deficient in mice lacking mGluR1. After he returned to Japan, Aiba and co-workers created a mouse strain in which mGluR1 is expressed only in cerebellar Purkinje cells (Ichise et al 2000).…”
Section: Long-term Depression (A) Discovery Of Ltdmentioning
confidence: 90%
“…Retrograde synaptic suppression triggered by postsynaptic mGluR1 activation It has been shown that bath application of mGluR1 agonists to a cerebellar slice induces presynaptic inhibition of excitatory inputs to Purkinje cells (Conquet et al 1994;Maejima et al 2001). However, since mGluR1 is not detected at excitatory presynaptic terminals in immunoelectron microscopic studies (Baude et al 1993;Nusser et al 1994;Petralia et al 1998;Lopez-Bendito et al 2001), how mGluR1 agonists affect glutamate release from presynaptic terminals was a puzzling problem.…”
Section: Endocannabinoid Signalling (A)mentioning
confidence: 99%
“…A key event in LTD induction is the activation of postsynaptic metabotropic glutamate receptors (mGluRs) (Rose and Konnerth, 2001). Mice null mutant for mGluR1, a subtype of mGluRs that is expressed in Purkinje cells (Martin et al, 1992;Gorcs et al, 1993;Ryo et al, 1993), exhibit severe cerebellar symptoms such as ataxia and motor discoordination and lack LTD (Aiba et al, 1994;Conquet et al, 1994). The behavioral relevance of Purkinje cell mGluR1 for proper cerebellar function was elegantly and unequivocally confirmed by the selective rescue of mGluRs in Purkinje cells of mGluR1 null mutant mice (Ichise et al, 2000), which restored both LTD and locomotor activity.…”
Section: Introductionmentioning
confidence: 85%
“…Recently, data from genetic knock-out experiments have distinguished between mGluRs 1 and 5 in cerebellar function. Mice deficient in mGluR1 show severe motor coordination problems and ataxia (Aiba et al, 1994;Conquet et al, 1994), whereas motor coordination appears normal in mice lacking mGluR5 (Wojtowicz et al, 1996). Basal ganglia function in these knock-out mice has not been examined as yet.…”
Section: Discussionmentioning
confidence: 99%